Kode dan Makna Komunikasi - Febby Ayu Syahputri Gurning; Sallimah Ika Putri Malau; Suhairi Suhairi (El-Mujtama: Jurnal Pengabdian Masyarakat, 2022)
Symbols iand isocial iinteraction icannot ibe iseparated iin ithe istudy iof icommunication. iThe iuse iof isymbols iis ian iactivity ithat iwill ialways ibe ipresent iin ievery icommunication iprocess. iThe icommunication ireview ifor iresearch ion ithe imeaning iof ithis isymbol iis ialways ichanging iwith ithe itimes. iThe ipattern iof ichanges iin isocial iinteraction iamong ithe icommunity iwill ibring iabout ia ichange iin ithe imeaning iof ithe isymbols icontained itherein. IThe ipurpose iof ithis iresearch iis ito iexamine ithe irelationship ibetween icode iand imeaning iin icommunication. iThe iresults ishowed ithat ihumans idevelop ia icomplex iset iof isymbols ito igive imeaning ito ithe iworld iin ia iparadox.